Attitudes of public and private high school students of Miag-ao towards UPV College students and the stereotype traits and characteristics associated with UPV students. - Vicente, Josephine P
This study determined the attitudes of public and private high school students of Miagao toward UPV college students. It also identified the physical characteristics and stereo-type group affiliation attributed to UPV College students by the respondents. The respondents were high school students in different year levels of both public and private schools. Selection of respondents is done through stratified random samling with proportional allocation. The pretest was administered to 78 private high school students of the Sacred Heart Academy 90 public high school students of Zarraga National School. The final test was given to the 54 private high school students of Marillac Academy and 169 public school students of Southern Iloilo Polytechnic College. The research instrument employed for the measurement of Student's attitude is semantic differential scale. A checklist is used in the identification of UPV College student's physical characterisitcs and stereotyped group affiliation as associated by the respondents. High school students in public and private schools and in different year levels have ambivalent attitudes toward UPV college students. The null hypothesis that there is no difference between the attitudes of public and private high school students is accepted as shown by the Mann-Whitney U test at 5 level of significance. The Kruskal Wallis one way analysis of variance with 1 degree of freedom showed no difference in the attitudes of high school students in different year levels. UPV students are described by private high school students as plansado ang bayo, ga maong, seksi, sunod sa uso, etc., and by public school students as ga-maong, plansado ang bayo, ga-rubbershoes, mahamot, etc. Public school students affiliate the studentry with Katoliko, human rights advocate, freedom fighter, etc.; and private school students associate UPV students with human rights advocate, freedom fighter, aktibista, etc. First year students described UPV students as ga-maong, ga walking shorts, ga tuck-in, etc; second year students as plansado ang bayo, shiny ang buhok, seksi, etc; Third year students as maniwang, plansado ang bayo, sunod sa uso, etc.; fourth year students as ga-rubbershoes, ga-maong, mahamot, etc. Also, first year students affiliate the studentrywith the groups of katoliko, anti-base militar, Pol. Sci. majors; second yeaar students with freedom fighter, human rights advocate, anti-base militar, Katoliko, DYMB Fans Club; and, fourth year students with human rights advocate, freedom fighter, Katoliko and Women's Liberation Movement.